“Green Aisyiyah” : Praksis Ekofeminis Gerakan Aisyiyah dalam Mengatasi Perubahan Iklim di Indonesia - Ramli, Amaliatulwalidain; Kencana, Novia; Melinda, Melinda (Jurnal Pemerintahan dan Politik, 2023)
This study aims to identify the Green Aisyiyah Program as a realization of the eco-feminist idea of dealing with climate change in Indonesia. The Green Aisyiyah Program is a program initiated by the Division of the Environmental Agency for Disaster Management (LLHPB), as one of the divisions within the structure of the Aisyiyah Movement. In elaborating this research, using qualitative methods with a phenomenological approach supported by Green Politics theory and ecofeminist theory. The results of the study explained that the Green Aisyiyah program is synonymous with empowering women to commit and contribute to protecting the environment in a sustainable manner in anticipation of climate change, various derivatives of the Green Aisyiyah program such as Green Ramadan, Green Eid al-Fitr, and Green Eid al-Adha were constructed through various activities that are very close to the daily lives and lives of women as agents of change because it cannot be denied that women are an important subject in access to natural resources, food and the environment.